Phytochemical Screening and Determination of Antioxidant Potential of Fruits Extracts of Withania coagulans - Vinoy Shrivastava2, Deepika Mathur1*, R.C. Agrawal1 and (Recent Research in Science and Technology, 2011)
In the present study, the phytochemical and antioxidant properties of methanolic and aqueous extracts of fruits of Withania coagulans were compared and investigated to find out the number of different phytoconstituents present in the plant which makes it remarkable for its use by traditional practitioners. Phytochemical screening of both the extracts showed the presence of alkaloids, steroids, phenolic compounds, tannins, saponin, carbohydrates, proteins, amino acids and organic acids. Further study showed high in vitro antioxidant activity in both of the extracts when compared to standard ascorbic acid but aqueous extracts showed higher antioxidant potential in comparison to that of methanolic extract.